'They rush you and push you too much … and you can't really get any good response off them': A qualitative examination of family involvement in care of people with dementia in acute care. (28th October 2015) - Moyle, Wendy; Bramble, Marguerite; Bauer, Michael; Smyth, Wendy; Beattie, Elizabeth
Abstract : Aim: To explore the role and needs of the family carer across different acute care contexts and their level of involvement in the care of their relative with dementia in this setting. Methods: A pragmatic, exploratory‐descriptive qualitative approach. A convenience sample of 30 family carers across three sites completed semi‐structured interviews. Results: Family carers wanted to be involved in the acute care of their family member with dementia. They acknowledged the importance of a central source of information, educated staff, guidelines on roles and processes, and positive communication, as well as respect from staff for the carer's knowledge of the older person and their needs. They also highlighted the need for medical staff to discuss with them the family member's treatment and care. Conclusion: There is a need for family‐focused interventions to improve communication and involvement of family in the care of family members with dementia in the acute setting.